2014
DOI: 10.1245/s10434-014-3567-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Epithelial-Mesenchymal Transition of Extracapsular Spread Tumors in Lymph Node Metastases of Head and Neck Cancer

Abstract: High EMT scores of ECS tumors in LNM predict an unfavorable prognosis and systemic dissemination more accurately than the simple presence of ECS in LNM in head and neck cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…These islands were also surrounded by CAF which were enriched for EMT‐promoting ligands. Lee et al investigated EMT marker expression in lymph nodes with and without ENE. They found that EMT was a better predictor of poor survival than ENE alone as ENE‐positive patients with a high percentage of tumour cells expressing mesenchymal markers had a five times worse survival rate compared to ENE‐negative patients.…”
Section: The Tumour Microenvironment In Enementioning
confidence: 99%
“…These islands were also surrounded by CAF which were enriched for EMT‐promoting ligands. Lee et al investigated EMT marker expression in lymph nodes with and without ENE. They found that EMT was a better predictor of poor survival than ENE alone as ENE‐positive patients with a high percentage of tumour cells expressing mesenchymal markers had a five times worse survival rate compared to ENE‐negative patients.…”
Section: The Tumour Microenvironment In Enementioning
confidence: 99%
“…In addition, a recent study on the role of epithelial-mesenchymal transition (EMT), which is a wellknown hallmark of metastatic potential, in the ENE of HNSCC supports our hypothesis. That study demonstrated that the extent or degree of EMT in ENE (rather than ENE in itself) was predictive of prognosis and survival (Lee et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…However, lymph node status classified by TNM staging system graduates in categories, in which important information might not be included and alone does not reliably predict prognosis . For example, extracapsular spread (ECS) is an additional pathological factor, which was recently integrated in the TNM staging system …”
Section: Introductionmentioning
confidence: 99%
“…9,10 For example, extracapsular spread (ECS) is an additional pathological factor, which was recently integrated in the TNM staging system. 8,11 Lymph node ratio (LNR), representing the number of positive lymph nodes to the total number of all resected lymph nodes, is an established predictor in cancers of other locations and entities including head and neck malignancies. 6,12,13 The concept of LNR seems to reflect the degree of lymph node metastasis more precise in regard to prediction of prognosis and therefore might be superior to classify metastatic spread by pN.…”
mentioning
confidence: 99%